The Influence of Communication, Work Discipline and Work Environment on Employee Performance at PT. PLN (Persero) South Medan Customer Service Unit (ULP) - Hidayat, Tifany Putri (Jurnal Sains dan Teknologi, 2023)
This study aims to analyze the effect of communication, work discipline and work environment on the performance of employees of PT. PLN (Persero) Customer Service Unit (ULP) South Medan. The total population in this study was 109 people, and by using the saturated sampling technique, a sample of 109 people was obtained. The analysis technique used is multiple linear regression. The results showed that communication had a positive and significant effect on employee performance at PT. PLN (Persero) Customer Service Unit (ULP) South Medan. Work discipline has a positive and significant effect on employee performance at PT. PLN (Persero) Customer Service Unit (ULP) South Medan. The work environment has a negative and significant effect on employee performance at PT. PLN (Persero) Customer Service Unit (ULP) South Medan. Communications, work discipline and work environment have a positive and significant effect on employee performance at PT. PLN (Persero) Customer Service Unit (ULP) South Medan. From the test results of the coefficient of determination, it is obtained that R Square for Y (employee performance) is 0.191. This means that 19.1% of employee performance variables are influenced by communication, work discipline and work environment and the remaining 80.9% is determined by other variables outside the contribution of this study. This is an open access article under the CC BY NC license